An exploration of school-community participation in the administration of public secondary schools in Katsina state, Nigeria - Zulaihatu Lawal, Bagiwa (International Journal of Physical and Social Sciences, 2015)
The study explored parents/community perception in relation to the administration of public secondary schools in Katsina State, Nigeria. The basic system theory designed by Bertalanffy (1968) was used to elicit information from the participants. The study employed a qualitative research methodology which involved collection of data through a semi-structured interview, in which two parents were purposively selected. The findings of the study showed thatthere exists an element of school/community participation in the management of public secondary schools in Katsina State which was through associations and organization, PTA meetings, extra-curricular and co-curricular activities, financial assistance, provision of both instructional and infrastructural facilities and in decision making. Based on the findings, the researcher recommends that the local and state government should work out modalities to create more avenues in which the parents and communities could be more committed to educational management in the area.